Crimes in the sphere of information and communication technologies - Ilya Viktorovich Kalyukarin (Вестник Северо-Кавказского федерального университета, 2022)
Information and communication technologies in the ratio about cybercrime are considered, concepts of information, information technologies, communications are considered. The concept of information and communication technologies is output.